2019
DOI: 10.1038/s41430-018-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between risk factors of metabolic syndrome with lung function

Abstract: Background/Objectives Increased evidence suggests that metabolic syndrome (MetS) is correlated with lung function impairment. This study aimed to explore the associations between MetS risk factors and the lung function. Subjects/Methods The cross-sectional study included 6945 participants attending health examination between 2010 and 2012 in Taiwan. MetS was assessed according to the criteria of National Cholesterol Education Program III. Spirometric parameters were measured to define lung function. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
6
13
1
Order By: Relevance
“…When each metabolic component was used to independently predict FVC (% predicted value), FEV1 (% predicted value), and the FEV1/FVC ratio, the result was consistent with that of previous studies [ 14 , 21 , 22 ]: after adjusting for age and family income group, WC was one of the MS components related to FVC and FEV1 reduction among men. To date, central obesity (abdominal obesity) is considered to be a common cause of metabolic and cardiovascular diseases in adults, including hyperglycemia, hypertension, and dyslipidemia.…”
Section: Discussionsupporting
confidence: 87%
“…When each metabolic component was used to independently predict FVC (% predicted value), FEV1 (% predicted value), and the FEV1/FVC ratio, the result was consistent with that of previous studies [ 14 , 21 , 22 ]: after adjusting for age and family income group, WC was one of the MS components related to FVC and FEV1 reduction among men. To date, central obesity (abdominal obesity) is considered to be a common cause of metabolic and cardiovascular diseases in adults, including hyperglycemia, hypertension, and dyslipidemia.…”
Section: Discussionsupporting
confidence: 87%
“…When we independently predicted FVC, FEV1 and FEV1/FVC ratio for each metabolic component, we found that after adjusting for age and family income group, WC was one of the MetS components associated with the decrease of FVC and FEV1 in males. This was consistent with some studies [13,20,21]. At present, it was believed that central obesity (abdominal obesity) was the source of common metabolic diseases and cardiovascular diseases in adults, such as hyperglycemia, hypertension, dyslipidemia and so on, and was the core component of MetS [22].…”
Section: Discussionsupporting
confidence: 90%
“…The most enriched terms for adipocytes included waist-hip ratio, cholesterol, inflammatory traits, and birthweight, whereas the most enriched terms for preadipocytes included atrial fibrillation and inflammatory traits. We also observed enrichments for traits with less apparent, but established connections to cardiometabolic traits, including forced expiratory volume, a measure of lung function that has been shown to be lower in individuals with metabolic syndrome and high body fat percentage [41,42], and intraocular pressure, which has been shown to be higher in individuals with metabolic syndrome and markers of obesity [43,44]. Taken together, we found that peaks in adipocytes contribute more to heritability of WHRadjBMI, whereas preadipocytes may contribute more to heritability of CAD, though to a lesser degree.…”
Section: Trait Heritability Enrichment Within Context-dependent Peaksmentioning
confidence: 72%